Consistency game: a didactic strategy for software engineering - Zapata Jaramillo, Carlos Mario; Duarte Herrera, Mary Inés (Rev. Téc. Fac. Ing. Univ. Zulia)
Software Engineering teaching has been traditionally worked with conventional methods like magisterial classes and practical projects. These strategies have been centered in teachers as learning sources, though they have permitted professional formation through four decades, but they apart student-centered learning strategies, like games, case studies, and simulations. In this paper we propose “Consistency Game”, a way to achieve students learning from a playful experience; the game works with the concept UML (Unified Modeling Language) diagrams consistency. UML is, nowadays, the most accepted standard for information systems modeling in Software Engineering.